Proteoglycans in health and disease: Novel regulatory signaling mechanisms evoked by the small leucine-rich proteoglycans - Iozzo, Renato V. (2010)
The small leucine-rich proteoglycans (SLRPs) are involved in many aspects of mammalian biology, both in health and disease. They are now being recognized as key signaling molecules with an expanding repertoire of molecular interactions affecting not only growth factors, but also various receptors involved in controlling cell growth, morphogenesis and immunity. The complexity of SLRP signaling and the multitude of affected signaling pathways can be reconciled with a hierarchical affinity-based interaction of various SLRPs in a cell- and tissue-specific context. Below, we review this interacting network, describe new relationships of the SLRPs with tyrosine kinase and Toll-like receptors and critically assess their roles in cancer and innate immunity.